Strategi Guru Pendidikan Agama Islam dalam Menerapkan Kurikulum Merdeka pada Pembelajaran di SD INPRES Kampus UNHAS Kota Makassar - Ode Wida; Andi Bunyamin; Andi Darmawangsa (UIN Fatmawati Sukarno Bengkulu, 2025)
The Strategies of Islamic Education Teachers in Implementing the Independent Curriculum in Learning at SD Inpres Kampus Unhas, Tamalanrea Sub-district, Makassar City. This research aims to: (1) examine the strategies for implementing the Independent Curriculum in Islamic education learning at SD Inpres Kampus Unhas; (2) assess the effectiveness of the Independent Curriculum application in Islamic education learning for students at SD Inpres Kampus Unhas. This study is descriptive qualitative research. Data collection techniques include observation, interviews, and documentation. The collected data were analyzed through three stages: (1) data reduction, (2) data presentation, and (3) conclusion drawing and verification. The validity of the data was ensured through source triangulation and technique triangulation. The observed sources include Islamic education teachers, the school principal, and students of SD Inpres Kampus Unhas. The findings of this study indicate that: (1) SD Inpres Kampus Unhas applies flexible planning, implementation, and assessment in learning using interactive methods and differentiation to meet students' needs. This is supported by formative and summative assessments for evaluation. Despite challenges, teacher collaboration and adaptability are key to successful learning. (2) The Independent Curriculum is effective in enhancing student engagement through interactive methods and differentiated approaches, although challenges remain in addressing students with learning difficulties. Overall, the curriculum fosters inclusive and adaptive learning environments. This indicates that the implementation of the Independent Curriculum can improve the quality of education by creating inclusive, adaptive, and student-centered learning environments. Despite the challenges, the flexible and collaborative approaches employed enhance student engagement and learning effectiveness.